Optimizing organic materials reduction from hazardous industrial bio-effluent by the aid of c/n enriched inoculum : an approach to use traditional anaerobic reactor to achieve environmental sustainability - Eugene, J. J.; M. Shahidul, Islam; Mamunur, R. (Publications International Lahore, Pakistan, 2019)
The aim of this paper is to present research conducted to increase organic materials reduction from waste bio-mass enriched palm oil mill effluent (POME). This POME is also known to be the hazardous bio-effluent responsible for the air, water and soil pollution. This research conducted to address the problem of poor performance experienced by the industries while using the anaerobic reactor for reducing effluent quality. The novelty of this research is of using C/N enriched inoculum (11<C/N< 40) in a two-stage continuous stirred tank reactor (CSTR) based anaerobic process at different pH for increasing COD reduction performance to a sustainable level. The research findings demonstrated that COD reduction has mostly occurred at the C/N of 20 to 32. The optimum level of COD reduction was 80% at C/N 32.5 with pH 7.0. The COD digestion performance as COD reduction was found significant at 95% level (p-value <0.05) with 53.2% input utilization factor (R2=53.2). The study concludes that POME digestion process for achieving higher COD reduction, CSTR based anaerobic.